Perceived corporate social responsibility, ethical leadership, and moral reflectiveness impact on pro-environmental behavior among employees of small and medium enterprises: A double-mediation model - Mansour, Mourad; Aman, Nida; Al-Ghazali, Basheer M.; Shah, Syed Haider Ali (Frontiers in Psychology, 2022)
Corporate social responsibility (CSR) is ever-evolving concept and gaining significance in the business world. This research proposes a research model that elucidates the mechanism by which Corporate social responsibility (CSR), ethical leadership and Moral reflectiveness promote pro-environmental behavior among employees of Small and Medium Enterprises (SMEs). in today's ever-changing environment, small and medium companies (SMEs) are critical for any economy to thrive and prosper. SMEs account for more than 30% of the GDP in Pakistan. However, little is known about the processes by which type of leadership influence the pro-environmental behavior, or the circumstances under which such impacts are strengthened or mitigated. The current study attempted to fill the gap by investigating a dual process model in which ethical leadership and a moral reflectiveness acted as two explanatory mechanisms in the impact of Corporate social responsibility (CSR) on pro-environmental behavior among employees working in Small and Medium Enterprises (SMEs). The structural equation modelling technique was used to test the research model's hypothesized relationships. A survey was used to collect data from 390 employees. Results showed that perceived CSR directly impacted moral reflectiveness and ethical leadership. Moreover, the moral reflectiveness and ethical leadership mediated the relationship between the perceived CSR and pro-environmental behavior. These findings contributed significantly to perceived CSR, ethical leadership, moral reflectiveness and pro-environmental behavior among employees by exploring the relationships among them. Practical implications and future research directions are also highlighted.